Absence of association of the Ala58Val (rs17571) CTSD gene variant with Parkinson's disease or amyotrophic lateral sclerosis in a Han Chinese population. (1st January 2018) - Xi, Jing; Yang, Xinglong; Zhao, Quanzhen; Zheng, Jinhua; An, Ran; Tian, Sijia; Huang, Hongyan; Hu, Fayunn; Ning, Pingping; Xu, Yanming
Highlights: This is the first study to detect the association between rs17571 and PD in Han Chinese population. CTSD rs17571 variant may not be associated with risk of PD in Han Chinese. CTSD rs17571 variant may not be associated with risk of ALS in Han Chinese. Abstract: Parkinson's disease (PD), amyotrophic lateral sclerosis (ALS) and Alzheimer's disease (AD) are neurodegenerative diseases that may share genetic risk factors. The exon variant Aal58Val (rs17571) in CTSD was recently associated with AD, leading us to examine whether it also affects risk of ALS and PD. The rs17571 variant was genotyped using the ligase detection reaction in 569 Han Chinese patients with PD, 301 patients with ALS, and healthy controls age- and gender-matched to each patient group. The frequencies of genotypes and alleles were similar between each disease group and its respective control group. Similar results were obtained when patients were stratified by gender, age at disease onset or type of symptoms at disease onset. These results suggest that the CTSD rs17571 variant may not be associated with risk of ALS or PD in Han Chinese.